Analysis of a Novel Four Level Flying Capacitor H – Bridge Converter - Gülpınar, Feyzullah; Sarı, Filiz; Uzun, Yunus (International Journal of Renewable Energy Development, 2018)
In this paper, a novel four-level flying capacitor inverter and its comparison with the conventional flying capacitor topology in terms of THD analysis are proposed. This new topology have some advantages over conventional one as following: The blocking voltages are the same for all switches used in the configuration, there is no need for capacitor midpoint connection and this eliminates low frequency current which circulate in dc-link capacitors, and the number of flying capacitor is reduced as compared with conventional form of it. The operation of the topology, modulation strategy, simulation results, and THD analysis for the output waveforms are presented in this paper.Article History: Received: 17th July 2017; Received: October 14th 2017; Accepted: Januari 18th 2018; Available onlineHow to Cite This Article: Gülpınar, F., Sarı, F., and Uzun, Y. (2017) Analysis of a Novel Four Level Flying Capacitor H – Bridge Converter. International Journal of Renewable Energy Development, 7(1), 71-75.https://doi.org/10.14710/ijred.7.1.71-75